The Impact of a Strike on the Attitudes and Behavior of a Rural Community - Gilson, Clive; Spencer, Ian; Granville, S. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper reviews the role and significance of the 1987-1988 Antigonish Bank Strike upon the rural community.